2014
DOI: 10.1590/s0103-84782014000600024
|View full text |Cite
|
Sign up to set email alerts
|

Percentual de suplementação de fonte taninífera na ração concentrada de caprinos jovens sobre o desempenho e carga parasitária

Abstract: RESUMO O presente estudo buscou determinar o percentual de adição de torta de pimenta rosa (TPR) na dieta de caprinos jovens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Considering that condensed tannins are identified as promising substances for the control of helminths ( ST T U et al, 2017;QUIJADA et al, 2015;QUIJADA et al, 2018;SHALDERS et al, 2014;SPIEGLER;LIEBAU;HENSEL, 2017;YOSHIHARA et al, 2013), the levels of condensed tannins present in 10 mg/mL HEB, may represent another important factor to justify the continuation of the present study.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering that condensed tannins are identified as promising substances for the control of helminths ( ST T U et al, 2017;QUIJADA et al, 2015;QUIJADA et al, 2018;SHALDERS et al, 2014;SPIEGLER;LIEBAU;HENSEL, 2017;YOSHIHARA et al, 2013), the levels of condensed tannins present in 10 mg/mL HEB, may represent another important factor to justify the continuation of the present study.…”
Section: Resultsmentioning
confidence: 91%
“…Effects such as reduction of hatchability, inhibition of development, and reduced motility of larvae and adults were observed in vitro (HOSTE et al, 2012). In vivo, they impair the oviposition of adult females in the digestive tract of ruminants, reducing the amount of eggs per gram of feces, which may favor reduction of contamination in the pasture (SHALDERS et al, 2014). Indirect anthelmintic action of condensed tannins is associated with immune stimulation consequent to better use of the dietetic protein content.…”
Section: Introductionmentioning
confidence: 99%
“…From these criteria, Operculina halmiltonii, commonly found in the North and Northeast regions of Brazil (Braga, 1960), has shown mixed results in antiparasitic efficacy tests (Almeida et al, 2007;Rodrigues et al, 2007;Gomes et al, 2010;Araújo et al, 2011;Brito-Júnior et al, 2011). The anthelmintic activity of this plant is attributed to the presence of condensed tannins in its composition , Nogueira et al, 2012, which may act by expelling parasites or reducing female fecundity (Shalders et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These differences may be because different parts of the plant were used and/or the soil and climate conditions differed during the sampling period (Furtado et al, 2013). Phytochemical analyses showed that the banana pseudoculm contains polyphenolic compounds, including tannins (Lans et al, 2000), which were previously described as anthelmintic agents (Gomes et al, 2010;Shalders et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Paolini et al (2003) (Shaik et al, 2006). Shalders et al (2014) registraram controle de parasitos gastrointestinais com máximo desempenho utilizando a adição de 20-30% de torta de pimenta rosa que é uma planta rica em TC na dieta de caprinos.…”
Section: Efeito Anti-helmíntico Do Tcunclassified